Pandemic and virtuality in higher education: Study of initial expectations in university students - Ramos, Valentina; Cuestas-Caza, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The study was carried out to determine differences in relation to expectations of virtuality due to pandemic in students of a public university. The results show significant differences taking into account gender (women indicated a greater inclination for visual tools), semester (students from the first and last semester had higher expectations compared to their colleagues from intermediate semesters) and level (there was more preference for educational tools linked to social networks in undergraduate students). This demonstrates the importance of adapting the training according to the needs, desires and interests of the students for a greater success of the process.